Changing Contemporary Scenario of India-Pakistan Relations: General Overview: भारत-पाक संबंध बदलता समसामयिक परिदृश्य : सामान्य अवलोकन - Suthar, Hukma Ram (RESEARCH HUB International Multidisciplinary Research Journal, 2022)
Recently, Pakistan released its new National Security Policy. This security policy outlines the thinking of the Pakistani system regarding the regional security environment and the threats to its national security. India has been mentioned prominently in this document. This reiterates the fact that Pakistan feels the biggest threat to itself is from India. It is also said in this document that geo-economic conditions will decide the geo-strategic orientation of Pakistan. However, given its ever-decreasing economic status, lack of connectivity with Central or South-East Asian markets, and increasing debt burden from China, Pakistan’s geo-economic ambitions appear to be failing before they can even take off. Now the question is, how should India’s national security system deal with this security strategy of Pakistan? Abstract in Hindi Language: अभी हाल ही में पाकिस्तान ने अपनी नई राष्ट्रीय सुरक्षा नीति जारी की ये सुरक्षा नीति, सुरक्षा के क्षेत्रीय वातावरण को लेकर पाकिस्तानी तंत्र की सोच और उसकी राष्ट्रीय सुरक्षा के खतरों का खाका पेश करती है। इस दस्तावेज में भारत का जिक्र प्रमुखता से किया गया है। ये इस बात को दोहराता है कि पाकिस्तान को अपने ऊपर सबसे ज्यादा खतरा भारत से ही महसूस होता है। इस दस्तावेज में ये भी कहा गया है कि भू-आर्थिक स्थितियां ही पाकिस्तान की भू-सामरिक झुकाव को तय करेंगी। हालांकि, अपनी लगातार घटती आर्थिक हैसियत, मध्य या दक्षिणी पूर्वी एशियाई बाजारों के साथ कोई संपर्क न होने और चीन से लिए गए कर्ज के बढ़ते बोझ के चलते, पाकिस्तान की भू आर्थिक महत्वाकांक्षाएं परवान चढ़ने से पहले ही ढेर होती दिखती हैं। अब सवाल ये है कि भारत का राष्ट्रीय सुरक्षा तंत्र, पाकिस्तान की इस सुरक्षा रणनीति से कैसे निपटे? Keywords: पाकिस्तान, भारत, रणनीति, वर्तमान।